2012
DOI: 10.17660/actahortic.2012.959.4
|View full text |Cite
|
Sign up to set email alerts
|

Major Guava Nematodes and Control Prospects Using Resistance on Psidium Spp. And Non-Host Crops

Abstract: The worst nematode problem affecting guava is that created by root-knot nematode, which is a recognized limiting factor in commercial guava production in Central and South America. Considering the difficulty of identifying Meloidogyne enterolobii (=M. mayaguensis) only by the perineal pattern, this species has been misidentified in different regions around the world and identified frequently as M. incognita or Meloidogyne spp. The species' identification is possible using esterase phenotype and molecular marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…identification, only M. enterolobii was detected in guava in Brazil (Siqueira et al, 2009). Carneiro et al (2012) found that P. guajava was a good host for M. enterolobii and a non-host for M. arenaria, M. incognita and M. javanica. Rossi et al (2002) observed similar results when three commercial guava cultivars were inoculated with M. incognita race 2 and M. javanica.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…identification, only M. enterolobii was detected in guava in Brazil (Siqueira et al, 2009). Carneiro et al (2012) found that P. guajava was a good host for M. enterolobii and a non-host for M. arenaria, M. incognita and M. javanica. Rossi et al (2002) observed similar results when three commercial guava cultivars were inoculated with M. incognita race 2 and M. javanica.…”
Section: Discussionmentioning
confidence: 99%
“…enterolobii has been misidentified in a number of surveys. It is probable that the severe root‐knot problem on guava in the Americas and the isolated cases in Africa and Asia involve only this particularly virulent species (Carneiro et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations